Apparent Half-Lives of Hepta- to Decabrominated Diphenyl Ethers in Human Serum as Determined in Occupationally Exposed Workers - Thuresson, Kaj (National Institute of Environmental Health Sciences, 2006)
The aim of the present study was to model apparent serum half-lives of polybrominated diphenyl ethers (PBDEs) with 7–10 bromine substituents. Workers with occupational exposure to PBDEs have elevated serum levels of PBDEs, but these substances are also found in the general population and are ubiquitous environmental contaminants. The calculations were based on exposure assessments of rubber workers (manufactured flame-retarded rubber compound) and electronics dismantlers who donated blood during a period with no work-related exposures to PBDEs, and referents without any known occupational exposure (clerks, cleaners, and abattoir workers). The workers had previously been found to have elevated levels of high- and medium-brominated diphenyl ethers compared with the referent populations. We performed nonlinear mixed-effects modeling of kinetics, using data from previous and present chemical analyses. The calculated apparent half-life for decabromodiphenyl ether (BDE-209) was 15 days (95% confidence interval, 11–18 days). The three nona-BDEs and four octa-BDE congeners were found to have half-lives of 18–39 and 37–91 days, respectively. BDE-209 has a short half-life in human blood. Because BDE-209 is commonly present in humans in general, the results of this study imply that humans must be more or less continuously exposed to BDE-209 to sustain the serum concentrations observed. BDE-209 is more readily transformed and/or eliminated than are lower brominated diphenyl ether congeners, and human health risk must be assessed accordingly.